Teacher perception of the implementation of personalized learning - Mulligan, Maureen Margaret (Kansas State University, 2021)
This study investigated teachers’ perceptions of the implementation of personalized learning. By understanding this specific case, suggestions on successfully implementing personalized learning in an elementary school in the Midwest became clear. The elementary school studied is one of the first schools in Kansas to join the KansasCan School Redesign project. This project is a reform effort initiated by the Kansas state Commissioner of Education, Randy Watson. Teachers from an elementary school facing a unique language barrier, poverty, and trauma were interviewed about their experiences pertaining to KansasCan Redesign. The study used a survey, as well as semi-structured interviews, to examine this particular case of Redesign. The school faced a number of challenges while attempting to Redesign, but ultimately found success in the use of teacher leadership and relationship building. The students at this elementary school began to see success in their academic learning. They ultimately felt more successful attending school than in a more traditional classroom setting, according to the teachers interviewed for this study. Not only did teachers think that students felt more successful through this process, but teachers also believed that parents became more involved due to Redesign. With so many variables affecting a school’s Redesign, it is essential to find actionable steps that schools can follow to be successful with such a reform. As more schools begin to Redesign it will be critical to continue research to understand what makes a school successful with this reform method.
Keywords: Educational reform; KansasCan Redesign; Personalized learning